Incomplete total body protein recovery in adolescent patients with anorexia nervosa. Issue 3 (16th March 2018) - Haas, Verena; Kent, Dorothea; Kohn, Michael R; Madden, Sloane; Clarke, Simon; Briody, Julie; Fischer, Felix; Müller, Manfred J; Gaskin, Kevin
ABSTRACT: Background: Bone health and growth during adolescence require adequate total body protein (TBPr). Renutrition for patients with anorexia nervosa (AN) should aim to normalize body composition and to recover both fat mass and TBPr. Objective: We intended to analyze predictors of protein status, including exercise status, in adolescents with AN and to investigate whether weight gain would replenish body protein deficits. Methods: We assessed TBPr in a longitudinal, observational study as height-adjusted nitrogen index (NI) using in vivo neutron activation analysis in 103 adolescents with AN [mean ± SD age, 15.6 ± 1.4 y; body mass index (BMI, in kg/m 2 ), 16.5 ± 1.6] at the commencement of inpatient refeeding (T0), in 56 of these patients 7 mo thereafter as outpatients (T1), and in age-matched controls (C; n  = 51, 15.5 ± 2.1 y, BMI 20.7 ± 1.9). Lean tissue and fat mass were assessed by dual-energy X-ray absorptiometry. BMI, BMI standard deviation score, and lean tissue mass were tested as predictors of protein status using receiver operating characteristic analysis. Results: At T0, NI was decreased in AN (AN, 0.88 ± 0.10 compared with C, 1.00 ± 0.08, P  < 0.001). In 34%, the patients showed protein depletion. Patients classified as ``exercisers'' had a higher NI than did ``nonexercisers'' (0.89 ± 0.11 compared with 0.85 ± 0.08, P = 0.045). BMI, BMI standard deviation score, and lean tissue mass did not show potential as predictors of protein status. Despite increases in weight (+6.9 ± 4.5 kg), and BMI (+2.5 ± 1.7), protein status did not improve (TBPr T0, 8.0 ± 1.1 kg; T1, 8.1 ± 1.0 kg, P  = 0.495). In an AN subgroup at 7 mo matched with controls in age (AN, 16.5 ± 1.1 y; C, 16.2 ± 1.8 y) and BMI (AN, 20.5 ± 1.4; C, 20.7 ± 1.3), protein status was still not normalized in AN (NI: AN, 0.89 ± 0.09 compared with C, 1.00 ± 0.07, P < 0.001). Conclusions: Adolescents recovering from AN remained protein depleted at 7 mo after baseline assessment, even though they were weight restored.